2022
DOI: 10.1101/2022.04.14.488421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First clinical validation of whole genome screening on standard trophectoderm biopsies of preimplantation embryos

Abstract: Whole genome screening is currently not available in preimplantation genetic testing (PGT) due to poor performance of whole genome amplification methods. Here, we present the first validation study using our latest whole genome amplification (WGA) protocol, which yields amplified DNA with comparable quality to genomic DNA when perfoming whole genome sequencing assays. We started by validating PGT for aneuploidy (PGT-A) using our WGA protocol on cell lines and donated human embryos, where amplification success … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We demonstrate that all mtDNA positions in the samples sequenced at 10X coverage have a mtDNA coverage of more than 100X except for one site. While prior studies have demonstrated the ability to identify mtDNA variants and heteroplasmy levels from WGS data 45,46 , integrating these into an all-in-one PGT method is an important step forward that makes PGT scalable and accessible.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that all mtDNA positions in the samples sequenced at 10X coverage have a mtDNA coverage of more than 100X except for one site. While prior studies have demonstrated the ability to identify mtDNA variants and heteroplasmy levels from WGS data 45,46 , integrating these into an all-in-one PGT method is an important step forward that makes PGT scalable and accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has attempted to evaluate the efficacy of whole-genome preimplantation genetic screening by comparing against born siblings and parents, attempting to statistically reconstruct the true genome of the child by identifying shared chromosomal segments [6] [7] . This screening has until recently only been available on a research but not clinical basis [8] . Imputing an embryo genome has many limitations, including that it cannot detect de-novo variants in an embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Since de novo variants have a substantial impact on disease pathogenicity, employing a technology to identify and characterize these variants before an affected pregnancy begins and before childbirth is highly meaningful. Orchid Health recently released the first clinically available whole-genome preimplantation screening (PGT-WGS) utilizing custom whole-genome amplification protocols [8] . While the precision and sensitivity of whole-genome sequencing on amplified DNA have been evaluated against known inherited variants, the ability to validate and quantify the detection of inherited variants without probe development as well as de novo variants has been limited until a child screened via PGT-WGS was born [7] .…”
Section: Introductionmentioning
confidence: 99%